2021
DOI: 10.1016/j.celrep.2021.109683
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile infection induces a rapid influx of bile acids into the gut during colonization of the host

Abstract: Clostridioides difficile infection induces a rapid influx of bile acids into the gut during colonization of the host Graphical abstract Highlights d Imaging mass spectrometry (IMS) is applied to study C. difficile infection (CDI) d IMS reveals a rapid influx of bile acids into the gut during CDI d The host then reduces transcriptional flux through bile acid biosynthesis pathways d Increased bile acids contribute to C. difficile spore germination and outgrowth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In addition, BAs are important regulators in the life history of Clostridium difficile . For example, the spore germination and outgrowth of Clostridium difficile are promoted by TCA (primary BA) but inhibited by DCA (secondary BA) ( Silverman et al., 2017 ; Abbas and Zackular, 2020 ; Theriot and Petri, 2020 ; Wexler et al., 2021 ). These findings were also supported by the correlation analysis of gut microbiota and BAs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BAs are important regulators in the life history of Clostridium difficile . For example, the spore germination and outgrowth of Clostridium difficile are promoted by TCA (primary BA) but inhibited by DCA (secondary BA) ( Silverman et al., 2017 ; Abbas and Zackular, 2020 ; Theriot and Petri, 2020 ; Wexler et al., 2021 ). These findings were also supported by the correlation analysis of gut microbiota and BAs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The generated DCA signals back to C. difficile to initiate biofilm production and maintenance in the host (Figure 8). Moreover, C. difficile could take advantage of high TA levels during the initial stages of infection not only for germination (63), but for generation of CA that can be used by other bacteria that do not encode BSH enzymes to generate DCA and persist in the gut environment and, potentially, to cause recurring infections.…”
Section: Discussionmentioning
confidence: 99%
“…C. difficile could take advantage of high TA levels during the initial stages of infection not only for germination(63), but for generation of CA that can be used by other bacteria that do not encode BSH enzymes to generate DCA and persist in the gut environment and, potentially, to cause recurring infections. by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
mentioning
confidence: 99%
“…Regardless, C. difficile encounters bile acid during colonization and its growth in the gut may impact bile acid synthesis in the liver. Taking advantage of MALDI imaging mass spectrometry, Wexler et al 51 found the levels of primary bile acids in the mouse gut increased significantly as early as one-day post-CDI. Additionally, the authors found that the introduction of cholestyramine, a bile-acid sequestering drug, lead to delayed C. difficile colonization.…”
Section: Bile Acid Metabolites and Their Role In C Difficil...mentioning
confidence: 99%
“…Additionally, the authors found that the introduction of cholestyramine, a bile-acid sequestering drug, lead to delayed C. difficile colonization. 51 Their results suggest that primary bile acids are required to efficiently establish C. difficile in a host.…”
Section: Bile Acid Metabolites and Their Role In C Difficil...mentioning
confidence: 99%